Implementation of Regional Regulation on Market Management in the Regulation of Morning Market Traders in Relation to Traffic Congestion in the Projo Ambarawa Market Area - Widya Kusumasari; Dani Muhtada Muhtada (Law Research Review Quarterly, 2026)
Traffic congestion in the Projo Ambarawa Market area indicates that traffic-related problems are not only associated with the increase in vehicle volume, but also with the governance of trading activities and the use of road space. This study aims to analyze the implementation of the Regional Regulation of Semarang Regency Number 9 of 2024 concerning the Establishment, Arrangement, and Development of People’s Markets, Shopping Centers, and Modern Retail Stores in the regulation of Morning Market traders, as well as to assess its effectiveness in addressing congestion issues in the market area. This research employs an empirical juridical method with a statutory approach, supported by primary data through the analysis of regional regulations, statutory laws and regulations, interviews, and field observations, as well as secondary data in the form of relevant literature. The results of the study indicate that the implementation of the Regional Regulation has been carried out administratively for traders within the market area through mechanisms of trader designation, issuance of Trader Identification Cards (KIP), regulation of trading facilities, and restriction of operating hours. However, in practice, Morning Market trading activities extend beyond the market area and involve various parties and sectoral authorities. This condition indicates that the exercise of authority tends to be understood as limited to the aspect of area management, such that the regulatory and enforcement functions have not fully encompassed all trading activities. As a result, the arrangement of Morning Market traders has not been fully effective in addressing congestion, as the existing problems arise from the interaction between economic activities, parking, and the movement of public transportation within the same spatial area. This study concludes that the main issue does not lie in the absence of norms, but rather in the implementation of authority that has not yet been integrated, particularly in distinguishing between